MENUMBUHKAN SIKAP SISWA DALAM PENCAPAIAN HASIL BELAJAR - Razali M. Thaeb (UIN AR-RANIRY, 2016)
Learning is change a person's ability and can be maintained within a certain time. Various growth that occurred in the study, such as changes in behavior after someone learners got a wide range of experience in various situations of learning itself, so the variety of experiences that will lead to the changes that occur in a person learners. While the measure is to apply the measuring instrument to a particular object. Magnitudes numbers obtained, then gained significance when compared to the results of measurements with a certain standard. The attitude of a person when used in learning and teaching a subject, then there will be individuals who love a subject (positive attitude) or behave otherwise is not like a subject (a negative attitude). For those students who have a positive attitude about a subject will learn them on their own and devote his full attention on a subject matter. In contrast the attitude of learners negative about a subject. Or in other words a learner who has a positive attitude toward a subject to be loved also a subject such and by itself learners will be serious in learning.